Impaired Barrier Function and Immunity in the Colon of Aldo-Keto Reductase 1B8 Deficient Mice - Wang, Xin; Khoshaba, Ramina; Shen, Yi; Cao, Yu; Lin, Minglin; Zhu, Yun; Cao, Zhe; Liao, Duan-Fang; Cao, Deliang (Frontiers in Cell and Developmental Biology, 2021)
Aldo-keto reductase 1B10 (AKR1B10) is downregulated in human ulcerative colitis (UC) and colorectal cancer, being a potential pathogenic factor of these diseases. Aldo-keto reductase 1B8 (AKR1B8) is the orthologue in mice of human AKR1B10. Targeted AKR1B8 deficiency disrupts homeostasis of epithelial self-renewal and leads to susceptibility to colitis and carcinogenesis. WT and AKR1B8 deficient mice were treated with FITC-dextran. Immune cells from colon were collected and analyzed by flow cytometry. Intestinal epithelial cells were collected and western blot and qPCR were applied for the protein and gene expression level. In AKR1B8 deficient mice, Muc2 expression in colon was diminished, and permeability of colonic epithelium increased. Within 24 hours, orally administered FITC-dextran was penetrated into mesenteric lymph nodes (MLN) and liver in AKR1B8 deficient mice, but not in wild type controls. In the colon of AKR1B8 deficient mice, neutrophils and mast cells were markedly infiltrated, γδT cells were numerically and functionally impaired, and dendritic cell development was altered. Furthermore, Th1, Th2 and Th17 cells decreased, but Treg and CD8T cells increased in the colon and MLN of AKR1B8 deficient mice. In colonic epithelial cells of AKR1B8 deficient mice, p-AKT (T308 and S473), p-ERK1/2, p-IKBα, p-p65 (S536) and IKKα expression decreased, accompanied with downregulation of IL18 and CCL20 and upregulation of IL1β and CCL8. Our studies showed AKR1B8 deficiency leads to abnormalities of epithelial cells and immunity in colon.